A New Transgenic Mouse Line for Imaging Mitochondrial Calcium Signals. Issue 3 (25th February 2021) - Redolfi, Nelly; Greotti, Elisa; Zanetti, Giulia; Hochepied, Tino; Fasolato, Cristina; Pendin, Diana; Pozzan, Tullio
Abstract: Mitochondria play a key role in cellular calcium (Ca 2+ ) homeostasis. Dysfunction in the organelle Ca 2+ handling appears to be involved in several pathological conditions, ranging from neurodegenerative diseases, cardiac failure and malignant transformation. In the past years, several targeted green fluorescent protein (GFP)-based genetically encoded Ca 2+ indicators (GECIs) have been developed to study Ca 2+ dynamics inside mitochondria of living cells. Surprisingly, while there is a number of transgenic mice expressing different types of cytosolic GECIs, few examples are available expressing mitochondria-localized GECIs, and none of them exhibits adequate spatial resolution. Here we report the generation and characterization of a transgenic mouse line (hereafter called mt-Cam) for the controlled expression of a mitochondria-targeted, Förster resonance energy transfer (FRET)-based Cameleon, 4mtD3cpv. To achieve this goal, we engineered the mouse ROSA26 genomic locus by inserting the optimized sequence of 4mtD3cpv, preceded by a loxP -STOP- loxP sequence. The probe can be readily expressed in a tissue-specific manner upon Cre recombinase-mediated excision, obtainable with a single cross. Upon ubiquitous Cre expression, the Cameleon is specifically localized in the mitochondrial matrix of cells in all the organs and tissues analyzed, from embryos to aged animals. Ca 2+ imaging experiments performed in vitro and ex vivo in brain slices confirmed the functionality of the probe in isolated cells and live tissues. This new transgenic mouse line allows the study of mitochondrial Ca 2+ dynamics in different tissues with no invasive intervention (such as viral infection or electroporation), potentially allowing simple calibration of the fluorescent signals in terms of mitochondrial Ca 2+ concentration ([Ca 2+ ]). :